Time trials predict the competitive performance capacity of junior cross-country skiers - Carlsson, M.; Carlsson, T.; Hammaerström, D.; Malm, C.; Tonkonogi, M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: This study investigated whether there is a correlation between time-trial performance and competitive performance capacity of male and female junior cross-country skiers and sought to explain sex-specific competitive performance capacity through multiple-regression modeling. Methods: The International Ski Federation`s (FIS) junior ranking points for distance (FISdist) and sprint (FISsprint) competitions were used as performance parameters. A total of 38 elite junior (age 18.5 ± 1.0 y) cross-country skiers (24 men and 14 women) completed 3 time-trial tests: a 3-km level-running time trial (TTRun), a 2-km moderate uphill (1.2° slope) roller-skiing time trial using the double-poling technique (TTDP), and a 2-km uphill (2.8° slope) roller-skiing time trial using the diagonal-stride technique (TTDiag). The correlations were investigated using Pearson correlation analysis, and regression models were created using multiple-linear-regression analysis. Results: For men, FISsprint and FISdist were correlated with the times for TTRun, TTDP, and TTDiag (all P < .001). For women, FISsprint was correlated with the times for TTRun (P < .05), TTDP (P < .01), and TTDiag (P < .01), whereas FISdist was correlated only with the times for TTDP (P < .01) and TTDiag (P < .05). The models developed for FISdist and FISsprint explained 73.9-82.3% of the variance in the performance capacity of male junior cross-country skiers. No statistically valid regression model was found for the women. Conclusions: Running and roller-skiing time trials are useful tests for accurately predicting the performance capacity of junior cross-country skiers.